Families in economically hard times : experiences and coping strategies in Europe (Bingley, U.K. : Emerald Publishing Limited, 2019)
The purpose of the edited collection Families in Economically Hard Times: Experiences and Coping Strategies in Europe is to provide readers with unique sociological knowledge on European families' experiences and behavioural strategies a decade after economic crisis of the 21st century. The particular importance of the topic is conditioned by the reality the last economic crisis created. This new reality has diverted from the previous; and as new phenomena emerge new coping strategies must also be created, as the old may not necessarily work. Hardships, functional solidarity, and issues of vital human needs - including practices of co-residence, sharing of money, food acquisition - have been explored in Families in Economically Hard Times: Experiences and Coping Strategies in Europe. Prominent scholars from Europe have joined efforts and, based on their latest researches, seek to answer the question: how challenges emerged during recent economically hard times influenced way of life of European families? The scholars of this book have used quantitative and qualitative research methodologies to create a varied and all rounded approach to answering this very question.
Introduction / Vida Česnuitytė, & Gerardo Meil -- Part I. Economic hardships experienced by families -- Chapter 1. What are the family characteristics that better help to cope with the economic crisis? Evidence from a large population survey in Italy / Sara Mazzucchelli, & Miriam Parise -- Chapter 2. Social inequality and intergenerational solidarity in European welfare states / Ronny König, Bettina Isengard, & Marc Szydlik -- Chapter 3. The influence of children on inequality in employment between men and women: the case of Spain / Diego Dueñas Fernández, & Almudena Moreno Mínguez -- Chapter 4. Material deprivation and personal wellbeing of single mothers in Lithuania / Aušra Maslauskaitė, & Ernesta Platukytė -- Part II. Families' strategies against economic hardships -- Chapter 5. Expectations and reality of support sharing within personal networks in economically hard time: the case of Lithuania / Vida Česnuitytė, & Eric D. Widmer -- Chapter 6. Deprivation and transfers between three generations: a regional analysis across Europe / Christian Deindl, & Martina Brandt -- Chapter 7. Here to stay? Intergenerational spatial proximity in Europe / Bettina Isengard, Ronny König, & Marc Szydlik -- Chapter 8. Below the breadline: families and food in Austerity Britain / Rebecca O'Connell, Abigail Knight, & Julia Brannen -- Chapter 9. Mothering and food acquisition in times of austerity: individual versus collaborative responses in the UK and Italy / Benedetta Cappellini, Vicki Harman, Alessandra Marilli, & Elizabeth Parsons -- Conclusions: Lives of families in face of economic crisis in Europe / Gerardo Meil, & Vida Česnuitytė.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Families -- Economic aspects -- Europe; Europe -- Social conditions -- 21st century; Europe -- Economic conditions -- 21st century; Business & Economics -- Economic Conditions; Economic & financial crises & disasters